(untitled) (World Economics and Finance Bulletin, 2024)
In the unexpectedly evolving virtual platforms of Iraq, information how clients interact with brands on social media and digital marketing systems is important for effective branding. This examine explores customer behaviors and choices closer to social media usage, brand engagement, and perceptions of virtual marketing, supplying insights into the factors that pressure a success digital branding techniques within the vicinity